Kurikulum Pendidikan di SD dan SMA Pada Masa Orde Baru - Andi Tati (Jurnal Pendidikan Sejarah, 2015)
The new order lasts from 1968 to 1998 , and can be regarded as the era of national development . In the field of development of education , especially primary education , there is a significant leap in the presence of Presidential Decree (Presidential Instruction) Basic Education . The implementation of education in the new order turned out to be many obstacles , because the new order brings educational ideology of “ uniformity “ that compress the progress in the field of education . In the new order of educational equality in education can not be created because the elements dominating and submissive still very strong in the education pattern of the new order.